Inactivation of pathogens in poultry residues through composting - Torres V, Magdiel (2023)
The aim of the study was to inactivate pathogenic microorganisms through the composting process for 120 hours using residues of organic compounds in two proportions: C/N 25 composed of 25.31, 40.42 and 34.27% and C/N 35 for 44.61, 12.90 and 42.50% of bean straw, fresh sorghum forage and dry chicken manure, respectively. The variables analysed were temperature, microbial load (mesophilic aerobics, total and faecal coliforms) and reduction of Escherichia coli and Salmonella Typhimurium, artificially inoculated in three levels of the compost piles. The C/N 35 treatment reached the highest temperature and inactivation of the pathogenic microorganisms evaluated during the thermophilic phase of composting. The temperatures reached were not homogeneous between the levels of the piles, being lower in the upper level (p<0.000). This study suggests the implementation of composting as an efficient alternative for the disposal of poultry waste.